METODE STEGANOGRAFI BPCS MENGGUNAKAN PENDEKATAN FUZZY UNTUK MENENTUKAN NILAI THRESHOLD - , Rahmad Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bit-Plane Complexity Segmentation Steganography (BPCS) is a technique that utilizes the characteristics of the human visual system in which human vision can not distinguish the form of binary information in a complex pattern. One of the most important process in BPCS steganography technique is the process of determining the threshold value. In the pilot study of the BPCS steganography technique, determination of threshold values is done directly by the user, where the default value is 0.3. The determination of threshold values in this way is inefficient, because if the user enters an inappropriate threshold value may cause repetitive insertion of the data. Another problem is the use of Î± variables in calculating the value of bit-plane complexity. Variable Î± is not able to detect the distribution of black and white pixels in a bit-plane which has a certain periodic. As an example of bit-plane with a chessboard motif has a value of Î± = 1, which is the maximum value of Î±. Bit-plane with a chessboard motif has a distribution of black and white pixels are periodic and therefore can not be classified as a complex block. Error in determining the value of bit-plane complexity can affect the quality of the resulting stego-image. In this study, the determination of threshold values will use the fuzzy approach. Threshold value will be determined based on two inputs, the ratio comparison of messages and images and the average value of the bit-plane complexity. The determination of threshold values in this way, can make the process insertion faster. In addition, the use of Î² variables in calculating the complexity value of a bit-plane, the resulting complexity value will more precision and noise resulting from the insertion of the stego-image can be reduced.